NATURAL GEOMETRIES. Inhabiting the forest - Luis Miguel Cortes Sanchez; Francisco Javier Terrados Cepeda; Panu Savolainen (Disegnare con)
Today’s desire to return to nature harks back to past eras and highlights the importance of revisiting historical experiences in order to address this longing. In the twentieth century, the benefits of rural life inspired urban proposals such as the Garden City. After World War II, reconstruction and rural-to-urban migration transformed social ethics, fostering a reconciliation with nature and a demand for healthy spaces and influencing urban projects. This article critically analyses the suburban development of Tapiola (Finland), designed by OttoIivari Meurman in 1945, a landmark of post-war urbanism based on the ideals of the Garden City. Although its architecture did not always reflect the urban plan’s ideals of integration with the natural landscape, the Suvikumpu residential complex (1962–1969; 1974–1980), designed by Raili and Reima Pietilä, stands out as an outstanding example of harmony between architecture and nature. The research explores and assesses the landscape and housing design strategies of the two phases of the complex, highlighting the transition from the first to the second. While previous studies have ignored this second stage, this analysis addresses its substantial changes, assessing how they enriched the initial proposal and allowing a value judgement on the entire project. The methodology focuses on the analysis of graphic documentation from the archive of the Arkkitehtuurimuseum (the Museum of Finnish Architecture), highlighting ‘the architectural drawings as key in formalising relationships between architecture and nature. Suvikumpu emerges as a manifesto for an alternative way of doing architecture in harmony with the natural environment, claiming the relevance of these practices in current contexts. DOI: https://doi.org/10.20365/disegnarecon.33.2024.10